Rebooting the Immune System with High-Dose Cyclophosphamide for Treatment of Refractory Myasthenia Gravis - Drachman, Daniel B. (2008)
A small but important proportion of patients with myasthenia gravis (MG) are refractory to conventional immunotherapy. We have treated 12 such patients by “rebooting” the immune system with high-dose cyclophosphamide (Hi Cy, 200 mg/kg), which largely eliminates the mature immune system, while leaving hematopoietic precursors intact. The objective of this report is to describe the clinical and immunologic results of Hi Cy treatment of refractory MG. We have followed 12 patients clinically for 1–9 years, and have analyzed their humoral and cellular immunologic parameters. Hi Cy is safe and effective. All but one of the patients experienced dramatic clinical improvement for variable periods from 5 months to 7.5 years, lasting for more than 1 year in seven of the patients. Two patients are still in treatment-free remission at 5.5 and 7.5 years, and five have achieved responsiveness to immunosuppressive agents that were previously ineffective. Hi Cy typically reduced, but did not completely eliminate, antibodies to the autoantigen AChR or to tetanus or diphtheria toxin; re-immunization with tetanus or diphtheria toxoid increased the antibody levels. Despite prior thymectomy, T cell receptor excision circles, generally considered to reflect thymic emigrant T cells, were produced by all patients. Hi Cy treatment results in effective, but often not permanent, remission in most refractory myasthenic patients, suggesting that the immune system is in fact “rebooted,” but not “reformatted.” We therefore recommend that treatment of refractory MG with Hi Cy be followed with maintenance immunotherapy.